Implementasi Soil Bioengineering Terhadap Produksi Padi di Desa Tulus Rejo Kecamatan Pekalongan - Setiawan, Putra Fajar; Sutarni, Sutarni; Fitriani, Fitriani; Apriyani, Marlinda (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
The increase in rice production in river basins (DAS) often faces challenges in the form of a decline in land quality due to land erosion and soil structure degradation that has an impact on farmers' harvests. One of the approaches that is beginning to be developed to overcome this problem is the soil bioengineering technique, which is a vegetation-based soil conservation method that aims to resist erosion and improve the physical condition of the land naturally. This research aims to: (1) analyze the cost, receipt and income of rice farming in the Tulusrejo Village Watershed, (2) analyze the comparison of costs, production and income between soil bioengineering farmers, and (3) analyze the factors of rice production and the influence of soil bioengineering on rice production, (4) analyze the elasticity of rice production. The research was carried out in Tulus Rejo Village, Pekalongan District using the cluster random sampling method on 37 rice farmers in river basins (DAS). The data was analyzed using the Shapiro-Wilk, Mann-Whitney U test and the Cobb-Douglas linear regression model. The research results show that the implementation of soil bioengineering causes significant differences in total costs, production and income between the two groups of farmers. In addition, based on the regression results, it is known that the variables of land area, seeds, fertilizers and pesticides have a real effect on rice production, while soil bioengineering does not have a significant statistical effect. This finding indicates that the implementation of production inputs and the implementation of soil bioengineering techniques are effective in increasing rice production and are suitable for implementation as an environmentally friendly and sustainable land conservation strategy. The production elasticity value of 1,176 shows the condition of increasing return to scale, which means that the addition of production inputs proportionally will increase rice production output proportionally.